PERAN PETUGAS PERPUSTAKAAN DESA DALAM MENINGKATKAN PENGETAHUAN PENDIDIKAN ISLAM PADA ANAK USIA 6-12 TAHUN DI DESA SEKUDUK KECAMATAN SEJANGKUNG TAHUN 2022 - Winanda (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The role of librarians is to organize library services and management systematically, which means not just running the library at random. Therefore, a librarian is responsible for playing a role in increasing knowledge and intelligence through managing and providing information services in libraries, information centers or documentation centers. The purpose of this study was to explain the activities pursued by village librarians as well as the strategies of village librarians in increasing Islamic education knowledge for children aged 6-12 years in Sekuduk Village, Sejangkung District in 2022. The research approach used is a qualitative type of phenomenological research. Data collection techniques using interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data display and conclusions. The validity technique used is triangulation and member check. The results of this study indicate that the activities pursued by village librarians in increasing knowledge of Islamic education are buying or or providing books suitable for children, collecting, compiling, maintaining collection materials related to Islamic education, seeking book donations, and disseminating information sources to attract reader. In addition, the strategy adopted by village librarians is to improve library facilities and infrastructure, choose interesting reading materials for children.